HUBUNGAN KENAIKAN BERAT BADAN IBU HAMIL TRIMESTER KETIGA DENGAN KEJADIAN PREEKLAMPSIA DI UPTD PUSKESMAS UMBUNASI - Mastiur Julianti B (Universitas Pahlawan Tuanku Tambusai, 2022)
Preeclampsia is the onset of hypertension with proteinuria at gestational age of more than 20 weeks or immediately after delivery. Preeclampsia is a multisystem disorder in pregnancy that is characterized by endothelial dyspuncture, increased blood pressure, and proteinuria. due to glomerular failure, and edema due to increased vascular permeability. Objective: to determine the weight gain of third trimester pregnant women with the incidence of preeclampsia at the Umbunasi Health Center UPTD. Research Methods: The design of this research is an analytic survey with a cross-sectional approach in which data collection for the independent and dependent variables is carried out at the same time. The cross sectional study aims to determine the risk factors that can cause health problems in the community. In this study, researchers wanted to know the factors associated with preeclampsia in pregnant women at the UPTD Umbunasi Health Center in 2021. Results: Based on Table 4.1. It is known that from 70 respondents of third trimester pregnant women, 25 (35%) pregnant women did not gain weight, while 45 (45%) pregnant women experienced weight gain. From the results of the statistical test, it was obtained that = 0.0505, because p value = 0.0505 > 0.05, it can be concluded